Cytotoxicity and apoptotic DNA fragmentation evaluation of ethanolic extract of Phyllanthus niruri L. in Vero and primary feline testicular cells - Roslan, Rasydan Hadi; Choong, Siew Shean; Mohamed, Maizan; Abu Bakar, Md Zuki; Gilbert, Brenda Sabrina; Noralidin, Amalina; Izamin, Izzati; Mohd Sani, Nani Izreen (Penerbit UTM Press, 2024)
Phyllanthus niruri or Dukung Anak is native to Southeast Asia, particularly in Malaysia and has been used as traditional preparations and as health supplements. However, previous studies have found that P. niruri can impair the male reproductive functions. With booming population of stray animals within the community, a new controlling method that is more affordable and safer must be developed. This study was aimed to explore the safety of P. niruri as a male herbal contraceptive to be used in veterinary medicine as one of the non-surgical sterilisation methods. For the preliminary part of this ongoing research, we have investigated the cytotoxicity activity of P. niruri ethanolic extract on Vero and primary feline testicular cells (FTC) and DNA apoptotic activity in FTC. Phyllanthus niruri extract was prepared using cold maceration method in 50% ethanol. The FTC were prepared from feline testes obtained from post-routine castration from local private veterinary clinics, while Vero cells were obtained from the archived cells of Virology Laboratory, Faculty of Veterinary Medicine Universiti Malaysia Kelantan (FPV UMK). The MTT assay was performed to evaluate the cytotoxicity of these plant extracts on FTC and Vero cells. Apoptosis was assessed using DNA laddering assay on extracted DNA of the treated FTC cells and observed the DNA patterns in gel electrophoresis. The 50% cytotoxic concentration (CC50) of the ethanolic extract of P. niruri was a dose dependent. The DNA laddering assay revealed that the plant extract does not induce apoptosis in FTC. Therefore, the study outcomes indicated that the ethanolic extract of P. niruri is potentially safe for animal use. However, in vivo studies are required to confirm these findings.